2021
DOI: 10.3390/ma14195877
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Characterization at Surface and Subsurface of Iron-Based Buried Water Pipelines

Abstract: Water pipe surface deterioration is the result of continuous electrochemical reactions attacking the surface due to the interaction of the pipe surface with environments through the time function. The study presents corrosion characterization at the surface and sub-surface of damaged ductile iron pipe (DIP) and galvanized steel (GS) pipes which served for more than 40 and 20 years, respectively. The samples were obtained from Addis Ababa city water distribution system for the analysis of corrosion morphology p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…8 Corrosion is an electrochemical process where the metallic substance in the natural gas transmission pipeline (e.g., Fe in carbon steel pipe) generally undergoes oxidation alongside the reduction of aqueous protons in the presence of certain electrolytes. [10][11][12] The condensed water in natural gas in contact with CO2 and H2S creates an acidic environment which initiates and sustains corrosion. 4,6,12 Studies have shown that the corrosion rate has been found to be proportional to the amount of water content inside the pipe.…”
Section: Introductionmentioning
confidence: 99%
“…8 Corrosion is an electrochemical process where the metallic substance in the natural gas transmission pipeline (e.g., Fe in carbon steel pipe) generally undergoes oxidation alongside the reduction of aqueous protons in the presence of certain electrolytes. [10][11][12] The condensed water in natural gas in contact with CO2 and H2S creates an acidic environment which initiates and sustains corrosion. 4,6,12 Studies have shown that the corrosion rate has been found to be proportional to the amount of water content inside the pipe.…”
Section: Introductionmentioning
confidence: 99%